Evaluation of the Effectiveness of the Aceh BNNP Communication Strategy in Handling Marijuana Abuse in Lamteuba - Ajidan, Ajidan (Contemporary Journal of Applied Sciences, 2024)
Drug abuse, especially marijuana, in Lamteuba, Aceh Besar, is a serious problem that requires strategic handling from the Aceh Provincial National Narcotics Agency (BNNP Aceh). This study evaluates the effectiveness of BNNP Aceh's communication strategy in reducing drug abuse and identifies obstacles and concrete steps taken. Using a qualitative approach and descriptive analysis methods, data were collected through interviews, observations, and documentation from BNNP Aceh officials and local communities. The results show that the Grand Design Alternative Development (GDAD) program faces internal obstacles, such as limited infrastructure and funds, as well as external obstacles, such as low community participation and limited market access. In conclusion, BNNP Aceh's communication strategy needs to be strengthened by increasing community trust, cross-sectoral cooperation, and adjusting programs to meet local economic needs.